Determination of tool size based on hermite curve [electronic resource] - Norsu'aidah Amir, 1987-; Yeak, Su Hoe, 1971- (2012)
Thesis (Sarjana Sains (Matematik Kejuruteraan)) - Universiti Teknologi Malaysia, 2012